In vitro evaluation of a novel biofilm remover. Issue 4 (24th November 2014) - Hofer, D; Meier, A; Sener, B; Guggenheim, B; Attin, T; Schmidlin, PR
Abstract Objective To evaluate a novel device for its efficacy in removing experimental biofilm from root surfaces and its potential for concomitantly removing/roughening the surface substance. Methods and Materials A novel acrylic rotary device (biofilm remover, BR) was tested in vitro in three experiments: surface loss, surface roughness [positive controls: Perioset (PS) and Proxoshape (PR)] and biofilm removal [positive controls: ultrasonic (US) and PS]. Surface loss/surface roughness was evaluated for dentin samples instrumented for three 20 s periods. The calcium removed during instrumentation was analysed after each interval and cumulatively, using atomic absorption spectrophotometry (AAS). Surface roughness was measured using profilometric analysis. Biofilm removal was evaluated on dentin specimens coated with a 64.5 h 6‐species in vitro formed biofilm, after one 20 s treatment. Surface loss was analysed using anova with Scheffé post hoc test, and surface roughness/biofilm removal was analysed using Mann–Whitney test (all P ≤ 0.05). Results Significantly less substance loss [μg (±1 SD)] was observed with the novel device at all time points, both interval and cumulative (1.0 (±0.5) versus 9.3 (±3.2) PS and 9.9 (±1.9) PR at 60 s). Surface roughness [μm (95% CI)] was significantly lower for BR than for PS and PR [0.00 (−0.01, 0.08) 0.20 (0.16, 0.27) and 0.21 (0.19, 0.24) at 60 s]. Significantly less biofilm bacteria remained after treatment with both BR 4.5 (−0.1, 16.2) and US 1.9 (−0.2, 14.3), compared to PS 52 (27.9, 82.1). Conclusions The novel biofilm remover was less damaging to dentin surfaces, while removing biofilm at least as effectively as devices used in this study.